PERAN PEMERINTAH DAERAH DALAM IMPLEMENTASI KEBIJAKAN KESIAPSIAGAAN BENCANA PADA DESTINASI WISATA AIR HITAM DI KOTA PALANGKA RAYA - Selawaty, Desy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The Black Water Tourism Destination in Palangka Raya City is a nature-based tourist area that is highly vulnerable to various potential disasters, such as forest and land fires, floods, and water tourism accidents. These conditions require integrated disaster preparedness policies in tourism management. Local governments have a strategic role in implementing disaster preparedness policies to ensure tourist safety and the sustainability of tourist destinations. This study aims to analyze the role of local governments in implementing disaster preparedness policies at the Air Hitam Tourism Destination in Palangka Raya City, as well as to identify the supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach with data collection through in-depth interviews, field observations, documentation studies, and supporting questionnaires to members of the Air Hitam Tourism Awareness Group (Pokdarwis). Data analysis was carried out in stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the local government plays a role as a regulator, facilitator, and coordinator in the implementation of disaster preparedness policies. The facilitative role of the local government through training, simulations, and the provision of safety facilities has been proven to increase the knowledge, skills, and awareness of Pokdarwis regarding disaster risks. However, the implementation of policies still faces obstacles in the form of limited technical regulations, suboptimal continuous cross-sector coordination, and limited resources. This study concludes that the implementation of disaster preparedness policies at the Air Hitam Tourist Destination has had a positive impact on increasing the capacity and preparedness of Pokdarwis, but still requires strengthening of regulations, coordination, and program sustainability. The results of this study are expected to serve as a reference for local governments in formulating and implementing policies for the management of safe, resilient, and sustainable tourism destinations